2023
DOI: 10.31234/osf.io/bmfp6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Review of Psychological and Neuroscientific Research on Musical Groove (2006−2022)

Abstract: When we listen to music, we often feel the urge to tap our fingers, stomp our feet, or move our bodies. This pleasurable sensation of wanting to move one's body with the music has been termed "groove." Research on groove was initially conducted mainly in the fields of musicology, ethnomusicology and philosophy, and in the 2000s, researchers within the field of empirical psychology began to investigate the concept of groove and the characteristics of music associated with it. In the 2010s, studies of the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 242 publications
1
10
0
Order By: Relevance
“…2, B and C; see Supplementary Results). This inverse U-shape profile is well approximated with a quadratic function [online experiment: adjusted r 2 (33) = 0.73; MEG experiment: adjusted r 2 (33) = 0.67], confirming previous findings of moderately syncopated melodies inducing strongest wanting-tomove experiences (12,14,15,50,51). This behavior shows that motor engagement indexes neither temporal predictability (highest in the low-syncopated condition) nor temporal prediction errors (highest in the high-syncopated condition) but is compatible with the notion of a precision-weighted temporal prediction error computation (5,40).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…2, B and C; see Supplementary Results). This inverse U-shape profile is well approximated with a quadratic function [online experiment: adjusted r 2 (33) = 0.73; MEG experiment: adjusted r 2 (33) = 0.67], confirming previous findings of moderately syncopated melodies inducing strongest wanting-tomove experiences (12,14,15,50,51). This behavior shows that motor engagement indexes neither temporal predictability (highest in the low-syncopated condition) nor temporal prediction errors (highest in the high-syncopated condition) but is compatible with the notion of a precision-weighted temporal prediction error computation (5,40).…”
Section: Resultssupporting
confidence: 82%
“…Then, the experiment consisted of a listening task in which each of the 36 melodies was presented binaurally once to participants, in a randomized manner. After stimulus offset, participants reported on a keyboard the associated level of groove, defined as the extent to which they wanted to move to this music (9)(10)(11)(12)(13)(14)(15). They had 60 s to answer.…”
Section: Experimental Designs and Data Acquisition Experimental Desig...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pleasurable feelings are another characteristic of groove (Etani et al, 2023;Hosken, 2020;Janata et al, 2012;Stupacher et al, 2016;Witek et al, 2014). Witek et al (2014) showed that pleasure ratings changed in accordance with changes in the syncopation level of drum breaks.…”
Section: Introductionmentioning
confidence: 99%
“…Groove is a worldwide phenomenon of listening to music, which is defined as the urge to move induced by specific rhythmic patterns or music (Kawase et al, 2001;Madison, 2006;Senn et al, 2016); it is accompanied by positive feelings such as pleasure or enjoyment (Etani et al, 2023;Janata et al, 2012;Stupacher et al, 2016;Witek et al, 2014;Senn et al, 2020). Various regions and different cultures bear synonymous terminology of groove, for example, nori, a Japanese musical term that is related to the sensation of vertical and horizontal movement (Etani et al, 2018;Kawase & Eguchi, 2010), "balanço" in Brazilian or "lüpfig" in Swiss German (Senn et al, 2019).…”
Section: Introductionmentioning
confidence: 99%